Bakó Elemér hagyatéka a debreceni egyetemi könyvtár kézirattárában - Juha, Enikő (Gerundium, 2015)
THE LEGACY OF ELEMÉR BAKÓ IN THE ARCHIVE OF THE UNIVERSITY OF DEBRECEN. he legacy of Elemér Bakó (1915–2000), the former Department Head of the Library of Congress and famous researcher of Hungarians, is held in the archive of the University and National Library of the University of Debrecen since 2013. he essay reviews the main parts of the 20 boxes of archive materials, which contain important information for contemporary linguistic research.